EXAMINING THE INFLUENCE OF LABOR FORCE PARTICIPATION AND ISLAMIC HUMAN DEVELOPMENT INDEX ON POVERTY: A PANEL DATA REGRESSION ANALYSIS - Nurjihan, Nabilah; Faizi, Faizi (Islamic Economics Program, Faculty of Islamic Economics and Business, 2024)
Despite the continuous increase in the Human Development Index (HDI) in DKI Jakarta, the poverty rate remains fluctuating and even increasing. Labor Force Participation and the Islamic Human Development Index (I-HDI) play crucial roles in poverty alleviation. The objective of this study is to examine the influence of Labor Force Participation and the Islamic Human Development Index on poverty in the six administrative regions of DKI Jakarta for the period 2018-2022. In this study, labor force participation and I-HDI are considered as independent variables, while poverty serves as the dependent variable. The population of interest consists of the six administrative regions in DKI Jakarta for the specified period, and a saturated sampling technique is employed. Panel data regression analysis techniques are utilized to test the secondary data obtained from the Central Bureau of Statistics. The findings reveal that the dependent variable, namely poverty in the six administrative regions of DKI Jakarta, is partially and simultaneously influenced by the independent variables, namely labor force participation and I-HDI. This research contributes to the academic knowledge base, serves as a reference for other researchers, and provides valuable insights to the government and policymakers as foundational considerations in addressing the issue of poverty in the six administrative regions of DKI Jakarta.